The innovator's media dilemma: How journalists cover incumbents' adoption of discontinuous technologies - Lorenz Graf-Vlachy; Andreas König; Richard Banfield; Markus Rauch; Angelo Boutalikakis (Journal of Product Innovation Management, 2022)
We offer a new vantage to the literature on the role of infomediaries in incumbent firms' struggles to adopt discontinuous technologies: the perspective of news media. Specifically, we combine the discontinuous technology literature with studies on news media journalism to theorize that journalists cover an incumbent's new product introductions differently, depending on whether a given new product builds on a discontinuous technology or on the respective established, continuous technology. First, discontinuous-technology-based product introductions receive a greater volume of coverage than continuous-technology-based product introductions because journalists prefer covering issues that are novel, deviate from the conventional, and potentially strongly impact society. Second, the coverage of discontinuous-technology-based product introductions is more divergent in tenor than the coverage of continuous-technology-based product introductions, as journalists seek to present opposing and thus more engaging opinions. Our analyses of unique archival data from two samples of product introductions in the automotive and photography industries, respectively, support our hypotheses. We also find intriguing indications that news media coverage of new products introductions using hybrid technologies is significantly context-dependent. Overall, our study points to so-far undescribed, media-related dilemmas for incumbent firms that aim to adopt discontinuous technologies.
Keywords: 650; discontinuous technological change; incumbent; social evaluations